Prevalence and patterns of pediatric surgical pathologies in three referral hospitals in Cameroon - Nwandum, Pascal; Mantho, Pauline; Mbapah, Leslie Tasha; Fongod, Edna; Ayaba, Tchiazah; Tsague, Midrelle Syntyche; Obi, Cyril Egbe; Oponde, Dieudonne Njibili; Mbi, Valerie Egbe; Tanue, Elvis; Ngowe, Marcelin Ngowe (Frontiers in Surgery, 2025)
BackgroundLittle is known about the spectrum and caseload of surgically managed pediatric conditions in Cameroon. This study describes the prevalence and patterns of pediatric surgical pathologies in three major hospitals across two regions in Cameroon.MethodsA hospital-based retrospective descriptive analysis of children aged ≤18 admitted for surgical conditions at the General Hospital, Douala, Laquintinie Hospital, Douala, and the Regional Hospital, Buea, from January 2019 to December 2021. Patient files and theatre registers were reviewed. A data extraction form was used to collect socio-demographic and clinical data. Data was analyzed using SPSS version 25.ResultsThere were 1,526 pediatric surgical cases, which made up 12.6% of all pediatric admissions during the study period. There was a male predominance of 63.5%. The age group 6–12 years was the most frequent, 26.2%. Neonates represented 7.3% of all pediatric surgical patients. Most of the patients presented as an emergency, 58.0%. About 36.0% of patients presented late with symptoms lasting more than 1 week to several months, with 14% already having complications on admission. Pediatric injuries (39.8%), congenital anomalies (25.6%), and gastrointestinal surgical pathologies (14.8%) were the most observed patterns of presentation.ConclusionSurgical pathologies constitute a significant proportion of pediatric admissions. Injuries, congenital anomalies, and gastrointestinal surgical pathologies are most frequently observed. Most children with surgical pathologies present late to the hospital with complications. Tailored measures to mitigate the burden of pediatric surgical pathologies are needed.